Multiple hypotheses about two mammalian upper dentitions from the Early Cretaceous of Australia. Issue 4 (1st October 2020) - Rich, Thomas H.; Flannery, Timothy F.; Evans, Alistair R.; White, Matt; Ziegler, Timothy; Maguire, Alanna; Poropat, Stephen; Trusler, Peter; Vickers-Rich, Patricia
Abstract: Two enigmatic, poorly preserved specimens of mammalian upper molars have been recovered from the Eric the Red West locality in Victoria, Australia. They are two of the three known specimens of mammalian upper molars from the Mesozoic of Australia. The two are quite different from one another. One is likely to be a tribosphenic mammal, the other may have a distant relationship to the monotreme or haramyid Kollikodon . Thomas H. Rich [trich@museum.vic.gov.au ], Timothy Ziegler [tziegler@museum.vic.gov.au ], Peter Trusler [peter@petertrusler.com.au ], Timothy F. Flannery [tim.flannery@textpublishing.com.au, Museums Victoria, PO Box 666, Melbourne, Victoria 3001, Australia; Alistair R. Evans [alistair.evans@monash.edu ], School of Biological Sciences, Monash University, Victoria 3800, Australia; Matt White [mwhite62@une.edu.au ], University of New England, Armidale, NSW 2351, Australia; Stephen Poropat [stephenfporopat@gmail.com ], Patricia Vickers-Rich [pat.rich@monash.edu ] School of Earth, Atmosphere and Environment, Monash University, Victoria 3800, Australia and Swinburne University of Science and Technology, Hawthorn, Victoria 3122, Australia; Alanna Maguire [maguire_alanna@hotmail.com ]